Performance evaluation and energy potential analysis of anaerobic membrane bioreactor (AnMBR) in the treatment of simulated milk wastewater - Siti Nur Fatihah, Moideen; Krishnan, Santhana; Yu-You, Li; Mimi Haryani, Hassim; Kamyab, Hesam; Mohd, Nasrullah; Mohd Fadhil, Md Din; Khairunnisa, Abdul Halim; Chaiprapat, Sumate S. (Elsevier Ltd, 2023)
An anaerobic membrane bioreactor (AnMBR) was employed as primary treatment unit for anaerobic treatment of simulated wastewater to produce high effluent quality. A lab scale hollow fiber membrane was used to scrutinize the performance of AnMBR as a potential treatment system for simulated milk wastewater and analyze its energy recovery potential. The 15 L bioreactor was operated continuously at mesophilic conditions (35 °C) with a pH constant of 7.0. The membrane flux was in the range of 9.6–12.6 L/m2. h. The different organic loading rates (OLRs) of 1.61, 3.28, 5.01, and 8.38 g-COD/L/d, of simulated milk wastewater, were fed to the reactor and the biogas production rate was analyzed, respectively. The results revealed that the COD removal efficiencies of 99.54 ± 0.001% were achieved at the OLR of 5.01 gCOD/L/d. The highest methane yield was found to be at OLR of 1.61 gCOD/L/d at HRT of 30 d with the value of 0.33 ± 0.01 L-CH4/gCOD. Moreover, based on the analysis of energy balance in the AnMBR system, it was found that energy is positive at all the given HRTs. The net energy production (NEP) ranged from 2.594 to 3.268 kJ/gCOD, with a maximum NEP value of 3.268 kJ/gCOD at HRT 10 d HRT. Bioenergy recovery with the maximum energy ratio, of 4.237, was achieved with an HRT of 5 d. The study suggests a sizable energy saving with the anaerobic membrane process.